The effectiveness of Animation-Cognitive Behavior Therapy (A-CBT) on Self-efficacy to Prevent Sexual Abuse among Children in Primary School of Surabaya City - Nurilla Kholidah; Ah Yusuf Ah Yusuf; Yuni S.A; Hendy M. Margono; Ely Rahmatika (International Journal of Nursing and Health Services (IJNHS), 2020)
The moral crisis is dangerous and threatening children in Indonesia. One of the biggest threats is sexual abuse. Children are vulnerable to becoming victims of sexual abuse because they cannot take care of themselves; children's ability to prevent sexual abuse can be done if the child has high self-efficacy. The purpose of this study was to examine cognitive behavioral therapy (A-CBT) on preventing sexual abuse among children. Method: A Quasi-experimental, pre-test, and post-test with control group design was applied in this study. Seventy samples were recruited by using simple random sampling and divided into experimental groups and control. The results showed that A-CBT has a positive effect on self-efficacy (p = 0,000). Further study needed to conduct the A-CBT for families, schools, and communities setting to ensure the effectiveness of this intervention